Q: What is the answer to 0 plus 0 plus 1 plus 1 plus 1 plus 1 plus 2 plus 2 plus 4 plus 4 plus 4 plus 4 plus 4 plus 5 plus 5 plus 5 plus 5 plus 6 plus 6 plus 6 plus 7 plus 7 plus 7 plus 7 plus 8?

Write your answer...

Submit

Related questions

100101 1 times 2^0 = 1 PLUS 0 times 2^1 = 0 PLUS 1 times 2^2 = 4 PLUS 0 times 2^3 = 0 PLUS 0 times 2^4 = 0 PLUS 1 times 2^5 = 32 EQUALS 37

43

The answer is 0.

1+-1= 0. 0+1=1 1+2=3 ps 3+4=7 7+8=15

4+4=8+0=8+1=9+1=10+0=10+1=11 It equals 11. You're welcome.

0=(9)2-(9-3)(root of 4)+3(2)

x2 + x + 1 = 0 ∴ x2 + x + 1/4 = -3/4 ∴ (x + 1/2)2 = -3/4 ∴ x + 1/2 = ± √(-3/4) ∴ x = - 1/2 ± (i√3) / 2 ∴ x = (-1 ± i√3) / 2

1 plus 1 plus 1 plus 1 equals 1 times 4. 1 times 4 equals 4. 4 minus 4 equals 0. 0

10 + 9 + 8 + 7 + 6 + 5 + 4 + 3 + 2 + 1 + 0 = 55

9

10 + 9 + 8 + 7 + 6 + 5 + 4 + 3 + 2 + 1 + 0 = 55

1 + 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 12 + 133 + 4 = 195

I was only able to get 13 but I think there can be more, this is what i got: 0+0+4=4 4+0+0=4 0+4+0=4 0+1+3=4 0+3+1=4 0+2+2=4 1+2+1=4 1+1+2=4 1+3+0=4 2+2+0=4 2+0+2=4 3+1+0=4 3+0+1=4

2 + 2 - 0 = 4

That is already in standard form. If you would like to express it in vertex form, that would be: 2x2 + x + 4 = 0 x2 + x/2 + 2 = 0 x2 + x/2 + 1/16 - 1/16 + 2 = 0 (x + 1/4)2 + 47/16 = 0

It is a quadratic equation and the values of x are -1/2 or -2/3Do you mean 12x2+14x+4 = 0If so then x = -2/3 and x = -1/2

Equation: kx^2 +x^2 +kx +k +1 = 0 Using the discriminant: K^2 -4*(k +1)*(k +1) = 0 Expanding brackets: k^2 -4k^2 -8k -4 = 0 Collecting like terms: -3^2 -8k -4 = 0 Dividing all terms by -1: 3k^2 +8k +4 = 0 Factorizing the above: (3k +2)(k +2) = 0 meaning k = -2/3 or -2 Therefore possible values of k are either: -2/3 or -2

-4+0-(-4)+(-4)-1= -4+0+4-4-1= -5

4(w^2 + 3w + 1)

2x2 - 6x + 4 = 0 2(x2 - 3x + 2) = 0 2(x - 1)(x - 2) = 0 x - 1 = 0 and x - 2 = 0 So, x = 1 and x = 2.

(3x + 4)(2x - 1) = 0 3x = -4 x = -4/3 2x = 1 x = 1/2 x = 1/2, -4/3

Negative plus a negative is a negative. Ex. -1+-1=-2 Negative times a negative is a positive. -2*-2=4 But a negative [minus] plus a positive [plus] can be minus, zero or plus: For example, -3 + 2 = -1 -3 + 3 = 0 -3 + 4 = +1

1 x 8 plus 0 x 4 plus 0 x 2 plus 1 x 1. Total 9

4+0=4 3+1=4 2+2=4 1+3=4 0+4=4 -1+5=4 -2+6=4 ...

(4-22) + (8-2) + (3-2) + 6 = (0) + (6) + (1) + 6 = 13* * * * * *here is a more detailed answer.2 squared is 4. so 4-4 is 0. 8-2 is 6. 3-2=1. and six. 0+6+1+6=13.the last answer was correct, but i thought id show you how to do it :). hope i helped!